Rio Seco, One of the First Freezer Plants of Chilean Patagonia. an Unknown Industrial Site in Magallanes - Correa-Baeriswyl, M (Institute of Physics Publishing, 2019)
During recent years, the valorization of architectural heritage has been an important subject of national debate in Chilean society. After decades of neglect, local heritage is achieving an important role in the country. In recent years, local legal regulations are evolving in order to guarantee a better heritage conservation. Even if listed heritage is increasing year by year in Chile, there are still several cultural sites not yet detected and studied. The present article exposes the main results of an historical research, related to the Freezer Plant of Río Seco, an historical industrial site located in Patagonia, at Río Seco district, near the city of Punta Arenas, in the South region of Chile, Magallanes. This site is not yet listed as heritage, even if it presents highly potential to be officially recognized. The Freezer Plant of Río Seco, was one of the first industries of its type in Magallanes Region. This plant was built in the beginning of the 20th century, founded by a British company operating in Chile at that time. This company was called The South American Export Syndicate, and it was conformed at London, England, in 1903. The industry of Río Seco processed sheep meat, for international export. When sheep breeding was successfully introduced in this Chilean region, exceeding internal consumption, different freezer plants were established in this territory. Río Seco was one of the first industries of this type. With the incipient technology of that time, frozen meet could last long periods of time, and reach far destinations in different continents by ship, as Europe and North America, starting from the plant s port at Chilean Patagonia.The installation of this Freezer Plant, started the conformation of a whole town, called Río Seco, where housing, and urban services were provided directly by the company to local workers. Due to its conformation and connections to the economic and urban history of Magallanes Region, this site can be considered as Chilean industrial heritage, with highly cultural interest. In spite of its historical value, the industrial site of Río Seco is not yet listed as national heritage. In recent decades, its decay has go on progressively. Spread the cultural relevance of this Freezer Plant and its history, could motivate its safeguard, and future conservation. © 2019 Published under licence by IOP Publishing Ltd.